2022
DOI: 10.3389/fvets.2022.929208
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gastrointestinal Helminth Infections in Rattus rattus, Rattus norvegicus, and Mus musculus in Chile

Abstract: Few studies have assessed the patterns of parasite populations of rodents over a longitudinal gradient in Chile. In this work, the gastrointestinal helminthic fauna of invasive rodents in Chile was examined to assess the association between their presence/absence and abundance with latitude, host sex, and host body condition, and to assess the coexistence and correlation of the abundance between parasite species. Rodents were obtained from 20 localities between 33 and 43°S. Helminths were extracted from the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Studies had reported that the prevalence and intensity of parasitism in vertebrates were often higher in males than females [ 3 , 4 , 5 ], and this had been named male-biased parasitism. On the other hand, female-biased parasitism [ 6 ] was also reported in the prevalence of parasites in invasive rodents from Chile [ 7 ] and wild bank voles ( Myodes glareolus ) [ 8 ]. Although sex-biased parasitism has different manifestations (female-biased or male-biased parasitism), the popular hypothesis is that the parasites will perform better within a male host [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies had reported that the prevalence and intensity of parasitism in vertebrates were often higher in males than females [ 3 , 4 , 5 ], and this had been named male-biased parasitism. On the other hand, female-biased parasitism [ 6 ] was also reported in the prevalence of parasites in invasive rodents from Chile [ 7 ] and wild bank voles ( Myodes glareolus ) [ 8 ]. Although sex-biased parasitism has different manifestations (female-biased or male-biased parasitism), the popular hypothesis is that the parasites will perform better within a male host [ 9 ].…”
Section: Introductionmentioning
confidence: 99%